Crime Stereotypicality and Severity Database (CriSSD): Subjective norms for 63 crimes - Freitas, Gonçalo (2022)
The existence of crime-related racial stereotypes has been well documented. People tend to associate certain groups with specific crimes, which, in turn, impacts criminal-sentencing decisions through the perceptions of crime severity. This evidence calls for regular updating of rating norms combining these variables. With this objective, and given that most of the normative studies provide norms for a small number of crimes and/or with an insufficient number of participants, a new norming study was conducted. Furthermore, norms from European countries are absent, and the existing ones (mostly with USA-based populations) do not simultaneously examine crime stereotypicality and crime severity. The Crime Stereotypicality and Severity Database (CriSSD) presents normative ratings for a set of 63 crimes on three dimensions: White stereotypicality, Black stereotypicality, and crime severity. The crimes were selected according to a comprehensive procedure. A total of 340 Portuguese participants (72.6% female; Mage = 26.86, SD = 7.65) answered an online survey. Each crime was evaluated by a range of 46–60 participants. Data allowed us to identify a crime typology with three clusters. We present descriptive data (means, standard deviations, and 95% confidence intervals) for each crime. Crime evaluations were associated with sociodemographic characteristics. Additionally, this study gives input regarding the understudied link between crime stereotypes and crime severity, showing that crime severity is predicted by ratings of both Black and White stereotypicality. The CriSSD (available at osf.io/gkbrm) provides a valuable resource for researchers in the field of social psychology to conduct studies with controlled materials on potential disparities in criminal-sentencing decisions.